HIIT'ing or MISS'ing the Optimal Management of Polycystic Ovary Syndrome: A Systematic Review and Meta-Analysis of High- Versus Moderate-Intensity Exercise Prescription - Richards, Cory T.; Meah, Victoria L.; James, Philip E.; Rees, D. Aled; Lord, Rachel N. (Frontiers in Physiology, 2021)
Introduction: Polycystic Ovary syndrome (PCOS) is a metabolic disorder associated with increased cardiovascular disease risk. Exercise is an effective treatment strategy to manage symptoms and reduce long-term health risk. High-intensity interval training (HIIT) has been suggested as a more efficient exercise mode in PCOS; however, it is not clear whether HIIT is superior to moderate intensity steady state exercise (MISS). Methods: We synthesized available data through a systematic review and meta-analysis to compare the effectiveness of isolated HIIT and MISS exercise interventions. Our primary outcome measures were cardiorespiratory fitness and insulin resistance, measured using V ̇O2max and HOMA-IR, respectively. Results: Moderate-quality evidence from 17 studies identified significant improvements in V ̇O2max following MISS (weighted mean [Δ] = 1.081 ml/kg/min, p < 0.001, n = 194), but not HIIT (Δ = 0.641 ml/kg/min, p = 0.128 n = 28). Neither HIIT nor MISS improved HOMA-IR ([Δ = -0.257, p = 0.374, n = 60] and [Δ = -0.341, p = 0.078, n = 159], respectively. Discussion: A significant improvement in V ̇O2max was evident following MISS, but not HIIT exercise in individuals with PCOS. This contrasts with previous literature in healthy and clinical cohorts that report superior benefits of HIIT. Therefore, based on available moderate-quality evidence, HIIT exercise does not provide superior outcomes in V ̇O2max compared with MISS, although larger high-quality interventions are needed to fully address this. Additional dietary/pharmacological interventions may be required in conjunction with exercise to improve insulin sensitivity.